Sentiment Analysis of Twitter Users Towards Kartu Prakerja Program Using the Naive Bayes Method - Wijaya, Harto Tomi; Kustiyono, Kustiyono (Indonesian Scientific Journal, 2024)
This study conducts a sentiment analysis of Twitter users regarding the Indonesian government’s Kartu Prakerja program, utilizing the Naive Bayes method for classification. Launched in 2020 to enhance employability skills amidst the COVID-19 pandemic, the program has garnered various public responses. A total of 836 tweets containing the keyword